The position of the PPAT Deed in its function as a means of evidence and its registration contains juridical defects - Islamy, Ayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Sale and purchase is an agreement that is made by an authentic deed made by a Land Deed Official (PPAT) which has perfect evidentiary power As an authentic deed, a PPAT deed must fulfil the procedures for making a PPAT deed as prescribed by law and other regulations. Making a PPAT deed must be made by an authorised official, namely a PPAT, because a PPAT deed made before a PPAT has a function as evidence and also as a condition for registration by a PPAT. The purpose of the research is to find out how the position of a PPAT deed made before a PPAT has evidentiary power as evidence for the parties and becomes a condition of registration of the deed if it contains juridical defects. The author conducts research with normative juridical research methods, descriptive analytical research typology, and qualitative data analysis techniques. Based on the results of the research, it is concluded that the PPAT deed has two functions, namely as evidence of certain legal acts regarding land rights and as a registration tool for changes in land registration data. When there is a transfer of land rights, the function of the PPAT deed as a registration tool is completed and leaves the PPAT deed as evidence of legal acts. The function of the PPAT deed is that it must be a requirement so that the transfer of land rights can be registered at the land office in accordance with the regulations regarding land registration and the implications of the juridical defects of the PPAT deed in the Decision result in the legal actions carried out, namely the sale and purchase, having no legal effect, the Sale and Purchase Deed is considered never to have been born even though it has been registered before, it has implications for the land office which requires to restore land rights. because it was previously registered by the land office to return to what it was before the Sale and Purchase Deed was born.